Unprecedented Observations of a Nascent In Situ Cirrus in the Tropical Tropopause Layer. Issue 4 (11th February 2021) - Reinares Martínez, I.; Evan, S.; Wienhold, F. G.; Brioude, J.; Jensen, E. J.; Thornberry, T. D.; Héron, D.; Verreyken, B.; Körner, S.; Vömel, H.; Metzger, J.‐M.; Posny, F.
Abstract: A nascent in situ cirrus was observed on January 11, 2019 in the tropical tropopause layer (TTL) over the southwestern Indian Ocean, with the use of balloon‐borne instruments. Data from cryogenic frost point hygrometer (CFH) and Compact Optical Backscatter and AerosoL Detector (COBALD) instruments were used to characterize the cirrus and its environment. Optical modeling was employed to estimate the cirrus microphysical properties from the COBALD backscatter measurements. Newly fomed ice crystals with radius <1 μm and concentration ∼500 L −1 were reported at the tropopause. The relatively low concentration and CFH ice supersaturation (1.5) suggests a homogeneous freezing event stalled by a high‐frequency gravity wave. The observed vertical wind speed and temperature anomalies that triggered the cirrus formation were due to a 1.5‐km vertical‐scale wave, as shown by a spectral analysis. This cirrus observation shortly after nucleation is beyond remote sensing capabilities and presents a type of cirrus never reported before. Plain Language Summary: Ice clouds are very common in the tropical tropopause layer, a layer of the atmosphere between 14 and 18 km separating the troposphere and the stratosphere. Ice clouds can be formed in situ, generated by cold temperature anomalies due to atmospheric disturbances. In this observational study, we use data from instruments that were flown on the same balloon on January 11, 2019 from Réunion Island, in the southwestern Indian Ocean. We report an ice cloud at the tropopause, at ∼16.5 km, composed of ice particles with a concentration of more than 500 per liter. This suggests that the ice cloud formed by homogeneous freezing, that is, the freezing of airborne aqueous solutions. In addition, an abrupt increase in ascent rate of the balloon is related to an atmospheric disturbance which cooled the air and possibly led to the ice cloud formation. The tiny size of the ice crystals indicates that they have just formed. This is a very rare observation because nucleation events are very short. Key Points: First in situ observation of a nascent tropical tropopause cirrus Homogeneous formation of tiny ice crystals (<1 μm) is due to a short vertical scale gravity wave at the tropopause Such optically thin cirrus clouds would be missed by current aircraft instruments/remote sensing systems